Cost-effectiveness analysis of oral anti-diabetic medications: DPP-4 inhibitor as monotherapy vs. combination therapy in type 2 diabetic patients in Malang, Indonesia - Oktaviana, Prita Aldilla; Triastuti, Efta; Yurina, Valentina; Che Hasan, Muhammad Kamil; Sidek Ahmad, Zulkhairul Naim (Universiti Putra Malaysia, 2025)
Background: Several anti-diabetic medications are covered under the Indonesian Universal Health Coverage (BPJS). However, metformin is typically prioritized over other options, such as DPP-4 inhibitors, because they are considered costly. DPP-4 inhibitors are often prescribed as an alternative to metformin when patients experience side effects, such as gastrointestinal discomfort and weight gain. This study aims to assess the cost-effectiveness of DPP-4 inhibitors in treating type 2 diabetic patients both as monotherapy and in combination with other oral anti-diabetic medications. Methods: Data were retrospectively collected from the medical records of diabetic patients treated at a hospital in Malang, Indonesia, known for prescribing DPP-4 inhibitors. A total of 87 medical records of ambulatory patients over 18 years old who had received DPP-4 inhibitors for at least three months were selected for analysis. Cost-effectiveness was assessed by calculating the average cost-effectiveness ratio (ACER). Results: The analysis revealed that the combination of DPP-4 inhibitor and metformin yielded the lowest ACER values for HbA1c (IDR 3,633) and fasting blood glucose (FBG) (IDR 3,230). In contrast, DPP-4 inhibitor monotherapy yielded the lowest ACER value for postprandial blood glucose (PPBG) (IDR 2,891). Additionally, the combination of DPP-4 inhibitor, metformin, and sulfonylurea yielded the lowest ACER values for reducing HbA1c (IDR 171,573), FBG (3,871), and PPBG (IDR 3,185) levels. Conclusions: The combination of DPP-4 inhibitor, metformin, and sulfonylureas was the most cost-effective treatment for reducing HbA1c, FBG, and PPBG levels. The combination of DPP-4 inhibitor and metformin and DPP-4 inhibitor monotherapy also showed competitive cost-effectiveness in achieving therapeutic targets.